2018
DOI: 10.24875/ciru.18000306
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue angiosarcoma of the breast in a patient with Klippel-Trenaunay-Weber syndrome

Abstract: Angiosarcomas are neoplasms of blood or lymphatic vessels with aggressive behavior. We report the coexistence of this malignancy within soft tissue of the breast in a 49-year-old woman who was diagnosed with Klippel-Trenaunay-Weber syndrome (KTW-S) during childhood. The patient has no previous history of radiation therapy on the chest and does not have any known risk factor for developing angiosarcoma, except for her congenital disease. To the best of our knowledge, the association between soft tissue angiosar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The cellulitis and bleeding rates noted are similar to our study (21% cellulitis; 17% bleeding) although we found a higher rate of ulceration (21%), potentially due to a greater proportion of adult patients in our cohort (mean age at presentation 23.8 years in our study compared to 14 years in the previous study). Documentation of skin cancer in the setting of KTS exists as case reports or survey studies only, and includes diagnoses of basal cell carcinoma, squamous cell carcinoma of the skin and angiosarcoma 7,8 . One prior study reported squamous cell carcinoma of the skin in conjunction with a large ulcer on the KTS‐affected lower limb 9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cellulitis and bleeding rates noted are similar to our study (21% cellulitis; 17% bleeding) although we found a higher rate of ulceration (21%), potentially due to a greater proportion of adult patients in our cohort (mean age at presentation 23.8 years in our study compared to 14 years in the previous study). Documentation of skin cancer in the setting of KTS exists as case reports or survey studies only, and includes diagnoses of basal cell carcinoma, squamous cell carcinoma of the skin and angiosarcoma 7,8 . One prior study reported squamous cell carcinoma of the skin in conjunction with a large ulcer on the KTS‐affected lower limb 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Documentation of skin cancer in the setting of KTS exists as case reports or survey studies only, and includes diagnoses of basal cell carcinoma, squamous cell carcinoma of the skin and angiosarcoma. 7,8 One prior study reported squamous cell carcinoma of the skin in conjunction with a large ulcer on the KTS-affected lower limb. 9 In our study, two patients had basal cell carcinoma and only one on a KTS-affected site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeted therapy has emerged as a current research focus. Presently, research has confirmed that tumor-targeting drugs such as sorafenib, sunitinib and pazopanib have certain therapeutic effects on angiosarcoma (7)(8)(9). However, due to the limited number of cases, designing clinical trials is challenging, and large-scale randomized controlled clinical trials are still lacking, resulting in the absence of a standard treatment plan.…”
Section: Introductionmentioning
confidence: 99%